EFEKTIVITAS MODEL PEMBELAJARAN TARI GOLEK ASMARANDANA KENYA TINEMBE DENGAN MEDIA DIGITAL UNTUK MENINGKATKAN KECERDASAN SPIRITUAL SISWA SMK SENI BUDAYA - Gusyanti (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
The 21st century learning is characterized by embracing rapid technological advances, therebyopening up ways for students to learn other than through teacher facilitation. This requiresstudents to learn creatively, yet not abandon the spiritual values as part of their characters. Thisresearch aims to develop a learning model for Golek Asmarandana Kenya Tinembe Dance usingdigital media to effectively increase the spirituality of students in vocational high schools in artsand culture. This research is a development research that adopts the Borg, Gall, and Gall models.The research subjects are students of class X at SMKN 1 Kasihan, Bantul, DI Yogyakarta. Modeldevelopment utilizes digital media with the Smart Apps Creator (SAC) application. Data wasobtained through questionnaires filled out by teachers and students. Data on the effectiveness oflearning model development research is qualitative and quantitative, obtained by means ofnormality tests and homogeneity tests. The conclusions of this research are: (1) The results ofthe normality test, the control class is at a significance level of α = 0.05 with a pre-test sig valueof 0.083 > 0.05 and a post-test sig value of 0.200 > 0.05, meaning it is normally distributed. Inthe experimental class, at the significance level α = 0.05 with a pre-test sig value of 0.200 > 0.05and a post-test sig value of 0.063 > 0.05, meaning it is normally distributed; (2) The results ofthe homogeneity test show that the Lavene Statistics pre-test value is 0.610 with a significancevalue of 0.437 > 0.05 and that the Lavene Statistics post-test value is 0.742 with a significancevalue of 0.391 > 0.05, so it can be concluded that they have the same variance (homogeneous);(3) Based on the independent sample test output with a post-test sig value of 0.000<0.05, it canbe concluded that H0 is rejected or there is a significant difference between the average of theexperimental class and the control class. Pembelajaran abad ke-21 memiliki ciri pesatnya kemajuan teknologi, sehingga terbuka lebar carabelajar siswa selain fasilitasi guru. Hal ini menuntut siswa harus belajar dengan kreatif namuntidak meninggalkan nilai spiritualitas bagian dari karakter. Penelitian ini bertujuanmengembangkan model pembelajaran tari Golek Asmarandana Kenya Tinembe dengan mediadigital untuk meningkatkan spiritualitas siswa SMK Seni Budaya yang efektif. Penelitian ini merupakan penelitian pengembangan yangmengadopsi model Borg, Gall, dan Gall.Subjek penelitian adalah siswa kelas X SMKN 1 Kasihan, Bantul, Yogyakarta. Pengembanganmodel memanfaatkan media digital dengan aplikasi Smart Apps Creator (SAC). Data didapatkanmelalui angket kepada guru dan siswa. Data keefektivan penelitian pengembangan modelpembelajaran berupa data kualitatif dan kuantitatif, yang didapatkan dengan cara uji normalitasdan uji homogenitas.Kesimpulan penelitian Efektivitas Pengembangan Model Pembelajaran Tari GolekAsmarandana Kenya Tinembe dengan Media Digital untuk Meningkatkan Spiritualitas SiswaSMK Seni Budaya, sebagai berikut: (1) Hasil uji normalitas, kelas kontrol pada taraf signifikansiα = 0,05 dengan nilai pretest sig sebesar 0,083 > 0,05 dan nilai posttest sig sebesar 0,200 > 0,05,artinya berdistribusi normal. Pada kelas eksperimen, pada taraf signifikansi α = 0,05 dengan nilaipretest sig sebesar 0,200 > 0,05 dan nilai posttest sig sebesar 0,063 > 0,05, artinya berdistribusinormal. (2). Hasil Uji Homogenitas, bahwa nilai lavene Statistic pretest sebesar 0,610 dengannilai signifikansi sebesar 0,437 > 0,05 dan bahwa nilai lavene Statistic posttest sebesar 0,742dengan nilai signifikansi sebesar 0,391 > 0,05 Sehingga dapat disimpulkan bahwa memilikivarians yang sama (homogen). (3). Berdasarkan output independent sampel test dengan nilai sigposttest sebesar 0,000< 0,05 sehingga dapat disimpulkan bahwa H0 ditolak atau terdapatperbedaan yang signifikan antara rata-rata kelas eksperimen dan kelas kontrol.